Study on the Resonant Suppression of Electrohydraulic Servo Shaking Table of a 2-Mass Dynamic System - Tao Wang; Jinchun Song (Shock and Vibration)
Since the load of electrohydraulic servo shaking table is an elastic load, there is a mutual coupling effect that exists between the experimental object and the shaking table, forming the resonance to weaken the dynamic characteristics, and producing resonant peak and resonant valley in the bandwidth required by the system, in which the amplitude is often larger than the stability range of acceleration’s amplitude. In this paper, the mathematical modeling of hydraulic power mechanism in a two-mass dynamic system is established based on electrohydraulic servo shaking table, yielding the frequency characteristic curve in accordance with the transfer function of the model. A multifrequency adaptive notch filter based on the least mean square algorithm is proposed to suppress the resonance, and the suppression effect of the resonance is simulated and verified in line with various values of load stiffness. Finally, the power spectrum is used to demonstrate the effectiveness of the multifrequency adaptive notch filter in the resonant suppression.